Isbat Nikah Pasangan Mualaf dalam Hukum Islam dan Hukum Positif di Indonesia - M. Alfar Redha (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
Marriage certificates are usually given to husbands and wives who have entered into a marriage contract according to Islam but are not legally registered by the state. In the end, the marriage has no legal force. As a result, when a problem arises in the marriage between the husband and wife, they cannot solve it legally because they need a marriage certificate. Marriage cases delegated to the Religious Courts to be confirmed marriages that have been held according to Islam but have yet to be known to the Marriage Registrar. This is different from the case in stipulation Number 14/Pdt.P/2017/PA.Jmb mentions a husband and wife marriage that was held according to Buddhism before both embraced Islam and without renewing the marriage contract according to Islam. This study aims to understand the juridical and normative considerations of the Panel of Judges in granting the request for confirmation of marriage and how to analyze the stipulation. This research is a case study using a normative-juridical approach. The data analyzed was carried out in a descriptive-analytical manner. The data that has been collected is obtained by interview and documentation methods. In this case, interviews were conducted with the Jambi Religious Court Judges, and documentation was in the form of several literature books and journals related to the research theme. The resulting research shows that the Panel of Judges granted the application for a marriage certificate in the determination based on the considerations of Article 2 paragraph (1) of Law Number 1 of 1974 concerning Marriage and the opinion of ash-Shafi'i as contained in the book al-Umm. This determination does not violate provisions in Islamic Law and Positive Law. In positive Law, there are no rules regarding the marital status of converts after converting to Islam, so this paper is expected to contribute material for consideration to complement the marriage rules in Indonesia so that it can make it easier for the Panel of Judges to determine similar cases. Keywords: Marriage Confirmation; converts; Islamic Law; Positive Law.